THE BLENDED LEARNING IMPLEMENTATION DURING THE COVID-19 PANDEMIC - Darmawan, Dendi; Salam, Urai; Sumarni, Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the application of the blended learning model to class X OTP 1 student at SMK Negeri 1 Pontianak during the Covid-19 pandemic. The learning system during the pandemic has turned into distance learning. One of the learning methods that are considered useful for distance learning was the Blended Learning method. This can be done to reduce the risk of transmission of covid-19 so as not to allow the meeting of teachers and students directly in the classroom. The research method used a descriptive research approach. The writer was taken data in this study through interviews and observations. The research subjects were class X OTP 1 teacher and representatives of class X OTP 1 students. The results showed that the application of the blended learning model in class X OTP 1 during the Covid-19 pandemic had been carried out starting from the lesson plan prepared by the teacher such as learning tools, and arranging learning schedules between face-to-face and face-to-face. Online, and teaching materials for blended learning. Blended learning assessment includes an assessment of attitudes, knowledge, and skills that are observed in online and face-to-face learning in a certain way. The conclusion from this study is that the application of the blended learning model in class X OTP 1 can be seen through planning activities, namely the teacher has prepared learning tools, schedules, and teaching materials. The action was with the blended learning syntax. Assessment activities are carried out face-to-face and online.